COLLABORATIVE GOVERNANCE DALAM GERAKAN CINTA ANAK BANTUL UNTUK MENUJU KABUPATEN BANTUL LAYAK ANAK - Andreas Deddy Eko Nugroho (Jurnal Riset Daerah, 2023)
Bantul Regency's acceleration efforts to achieve Kabupaten Layak Anak is through Gerakan Cinta Anak Bantul (Creating and collaborating attempt for "the children of Bantul"). This policy is identified by the Bantul Regency government as a Data Management Information System, Performance Process, Evaluation Media, and Accelerated Performance Results for Kabupaten Bantul Layak Anak, which involves many parties and multi-sectors. This research was conducted to describe the collaboration process between actors/parties in the implementation of Gerakan Cinta Anak Bantul. The type of research used is descriptive-qualitative research with data collected through participant observation. The results proven that 1) Kabupaten Bantul Layak Anak Program implementation has been obstructed by several things, both micro (reporting) and macro (implementation), 2) Actors collaboration process in the development of Gerakan Cinta Anak Bantul is carried out in the form of delegation, cooperation, communication, consultation, and networking, 3) Gerakan Cinta Anak Bantul implementations are through several stages, namely program analysis, necessity mapping, distribution, coordination, input, assessment, ranking, and reporting, 4) The existence of the Cinta Anak Bantul System has delivered Bantul Regency to Nindya rank in 2022 and Utama rank in 2023.